Troy Is Burning: Epic Archetypes - Alberto Camerotto (Clotho)
The paper discusses the Italian project on “Ilioupersis: Epic Archetypes,” which delves into the multifaceted concept of war violence across cultures and history, exploring its representation in various disciplines like literature, art, and cinema. Through seminars, conferences, and public actions, the project aims to enhance civil consciousness and collective memory, particularly focusing on the fall of Troy as a universal symbol of violence and its consequences. With a strong emphasis on engaging younger scholars and involving communities, the project seeks to foster a shared historical and cultural awareness around war violence themes. Moreover, it explores the transformative power of sport as a symbol of peace and cooperation, drawing parallels between ancient athletic ideals and contemporary societal values. Collaborations with institutions like UNESCO aim to extend these discussions to conflict-affected areas, promoting peace-building efforts through cultural understanding and dialogue. Ultimately, the project advocates for a civilization that values peace, understanding, and cooperation over violence and conflict.